ISLAMIC LEGAL ANALYSIS OF QARDHUL HASAN AGREEMENT IN BITUL MAL WA TAMWIL INTEGRATED JOINT BUSINESS SIDOGIRI BRANCH BAWEAN - Robi'in, M. (Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2023)
This study examines the role of Islamic Banks and Baitul Maal wa Tamwil (BMT), especially BMT UGT Sidogiri Bawean Branch, in supporting the community's economy through sharia principles. Islamic Banks act as financial intermediaries that comply with sharia principles, avoid usury, and transactions that contain uncertainty. As a sharia-based microfinance institution, BMT focuses on developing productive businesses and distributing zakat, infak, and sedekah funds to improve the quality of the community's economy, especially in the small and medium enterprise (SME) sector. This study uses a qualitative approach with a case study design to explore how BMT UGT Sidogiri Bawean Branch operates and overcomes challenges in implementing sharia principles. Data collection methods include in-depth interviews, participant observation, and document analysis, while thematic analysis is used to identify significant patterns and dynamics. The research findings indicate that although BMT UGT Sidogiri Bawean Branch has succeeded in providing interest-free loans through the Qardhul Hasan product, there are inconsistencies with sharia principles that need to be fixed. This study confirms the important contribution of Islamic Banks and BMTs in creating a fair and sustainable financial system, as well as their role in building a more inclusive and ethical economy.